IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH CONCEPT ORIENTED READING INSTRUCTION - Januarty, Restu (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2019)
The objcetive of this research aimed to improve the students reading comprehension at the level of literal and inferential comprehension. This research was a pre-experimental research, which employed one-group pretest-posttest. This research was conducted through three steps of process: pre-test, treatment and post-test to investigate the improvement of the student’s reading comprehension through the implementation of CORI. Pretest was done to measure the students reading comprehension before conducting the treatment. The treatment, which was the teaching and learning process, was conducted in four meetings in which CORI was applied as method to improve the students reading comprehension. After the treatment, post-test was done to measure the students reading comprehension after the implementation of CORI. Location of this research is the seventh Grade students of SMP Negeri 7 Masamba, at academic year 2015/2016. The total numbers of subjects were 41 students, which were divided into 2 classrooms VII A and VII B. There is two variables of this research; the use of CORI as the independent variable and reading comprehension is the dependent variable. In this research, reading comprehension test was the instruments to collect the data related to the student’s reading comprehension at the level of literal and inferential comprehension. The test consisted of multiple choices to assess the student’s literal comprehension and essay test to measure the student’s inferential comprehension. In testing the hypothesis, t-test was employed. The calculation was done by using SPSS v.20. In summary, CORI improved the student’s ability to understand and identify the explicitly or directly state the information given in the text; for example, the characters of the story, their traits, place and time where the story taken place, main ideas, details, cause and effect and sequences in the text. Following the improvement of the student’s literal comprehension, the student’s inferential comprehension was also improved.